Guideline for Surveillance and Investigation of West Nile Fever Under One Health Concept, Kanchanaburi, 2012 - Ardkhean, Wanchai; Lekcharoen, Paisin; Kuhapan, Surawat; Pradit, Pronpimon; Worasuwannarak, Metta; Wutthanarungsan, Rochana (Journal of Health Science of Thailand, 2017)
Thailand is vulnerable to outbreaks of West Nile fever. Thus, the public health, livestock and wildlife sectors in Kanchanaburi has joined to develop the surveillance and investigation of West Nile fever according to one health concept since 2012. The guideline include objective; scope; the definition of infection and case; surveillance in the human, birds, horses and mosquitoes; and the investigation in both human and animal case. There are four public health processes: (1) surveillance of encephalitis and meningitis cases, (2) active case finding in the hospital, (3) investigation and control in human, and (4) entomological study in mosquitoes. The livestock also have four processes, such as: (1) WNV surveillance in backyard poultry, (2) serological survey for WNV in horses, (3) investigation and control in domestic animal, and (4) laboratory surveillance for WNV. In case of wildlife processes, there are: (1) case and death bird surveillance, (2) collateral avian influenza and emerging diseases surveillance in wild birds, (3) investigation and control in wildlife, and (4) mosquito surveillance for WNV in bird residence. However, a joint team process cannot carry out. More should be done for team improvement is operating a West Nile virus’s public health emergency response plans exercise with the aim to be able to actually tackle the spread of the virus efficiently.